2018
DOI: 10.1194/jlr.m084202
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an acid sphingomyelinase ceramide kinase pathway in the regulation of the chemokine CCL5 [S]

Abstract: Acid sphingomyelinase (ASM) hydrolyzes sphingomyelin to produce the biologically active lipid ceramide. Previous studies have implicated ASM in the induction of the chemokine CCL5 in response to TNF-α, however, the lipid mediator of this effect was not established. In the present study, we identified a novel pathway connecting ASM and ceramide kinase (CERK). The results show that TNF-α induces the formation of ceramide 1-phosphate (C-1-P) in a CERK-dependent manner. Silencing of CERK blocks CCL5 production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…It was shown that p38 signaling was implicated in nSMase2 phosphorylation and activation 52 . Our data are corroborated by a previous study 40 showing that disrupting CERK activity by either NVP-231 or siRNA decreases the TNF-α-induced phosphorylation of p38 MAPK, JNK, and NF-κB. TNF-α binding to its cognate receptor on cell surface phosphorylates the downstream c-Jun and NF-κβ, resulting in the activation of several inflammatory genes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was shown that p38 signaling was implicated in nSMase2 phosphorylation and activation 52 . Our data are corroborated by a previous study 40 showing that disrupting CERK activity by either NVP-231 or siRNA decreases the TNF-α-induced phosphorylation of p38 MAPK, JNK, and NF-κB. TNF-α binding to its cognate receptor on cell surface phosphorylates the downstream c-Jun and NF-κβ, resulting in the activation of several inflammatory genes.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings specifically show that CERK inhibition or its downregulation in monocytic cells significantly blocks the production of critical inflammatory mediators including IL-1β and MCP-1. We reported previously in one of our study that knockdown of CERK led to a significant decrease in CCL5 mRNA and protein expression following TNF-α stimulation 40 . IL-1β and MCP-1 are the major proinflammatory mediators produced mostly by the activated monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 51%
“…It was previously shown that p38 signaling was implicated in nSMase2 phosphorylation and activation. Our data are corroborated by a previous study 31 showing that disrupting CERK activity by either NVP-231 or siRNA decreases the TNF-α-induced phosphorylation of p38 MAPK, JNK, and NF-κB. TNF-α binding to its cognate receptor on cell surface receptor phosphorylates the downstream c-Jun and NF-κβ, resulting in the activation of several inflammatory genes.…”
Section: Discussionsupporting
confidence: 91%
“…Ceramide kinase (CerK) phosphorylates ceramide to form ceramide-1-phosphate (C1P), a molecule involved in proliferation, migration and inflammation [ 37 ] via the production of several cytokines and chemokines [ 38 ]. C1P-enhanced pancreatic tumor cell migration and invasion are dependent upon PI3K, Akt1, mTOR1, ERK1-2, and RhoA/ROCK signaling pathways [ 39 ].…”
Section: Sphingolipids In Cancermentioning
confidence: 99%